2016
DOI: 10.1042/bst20150256
|View full text |Cite
|
Sign up to set email alerts
|

The Drosophila photoreceptor as a model system for studying signalling at membrane contact sites

Abstract: Several recent studies have demonstrated the existence of membrane contact sites (MCS) between intracellular organelles in eukaryotic cells. Recent exciting studies have also demonstrated the existence of biomolecular interactions at these contact sites in mediating changes in the membrane composition of the cellular compartments. However, the role of such contact sites in regulating organelle function and physiological processes remains less clear. In this review we discuss the existence of a contact site bet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 32 publications
0
19
0
Order By: Relevance
“…dPLD has been reported to be localized in the submicrovillar cisternae (LaLonde et al, 2005; Raghu et al, 2009), a specialization of the smooth endoplasmic reticulum that is positioned ca. 10 nm from the plasma membrane at the base of the microvilli (Yadav et al, 2016). At this location, dPLD might bind to the C-terminal tail of M either before or after it is endocytosed into RLV; binding of mammalian PLD1 has been reported to the C-terminal tail of several rhodopsin superfamily GPCRs including the 5-HT2 a , muscarinic and opioid receptors [(Barclay et al, 2011) and references therein].…”
Section: Discussionmentioning
confidence: 99%
“…dPLD has been reported to be localized in the submicrovillar cisternae (LaLonde et al, 2005; Raghu et al, 2009), a specialization of the smooth endoplasmic reticulum that is positioned ca. 10 nm from the plasma membrane at the base of the microvilli (Yadav et al, 2016). At this location, dPLD might bind to the C-terminal tail of M either before or after it is endocytosed into RLV; binding of mammalian PLD1 has been reported to the C-terminal tail of several rhodopsin superfamily GPCRs including the 5-HT2 a , muscarinic and opioid receptors [(Barclay et al, 2011) and references therein].…”
Section: Discussionmentioning
confidence: 99%
“…RDGBα is a membrane-associated protein (Yadav et al, 2015) with a highly restricted localization within PRs (Suzuki and Hirosawa, 1994;Vihtelic et al, 1993). Endogenous RDGBα is present on submicrovillar cisternae (SMC), a specialized ER compartment near the base of the rhabdomeral PM, an arrangement reminiscent of an ER-PM membrane contact site (MCS) (Yadav et al, 2016). In a recent study, rdgB mutants were shown to have defects in PI and PA turnover following activation of PLC signalling (Yadav et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…In contrast to mammalian tissue culture cells, in Drosophila photoreceptors, the single PITPNM is constitutively localized at the SMC a MCS between the ER and the PM [74]. There is no detectable change in this localization on receptor stimulation.…”
Section: (B) Localization Of Pitpnm Proteins To Membrane Contact Sitesmentioning
confidence: 84%
“…It has been proposed that the DG may be metabolised via liberation of polyunsaturated fatty acids (PUFA) that may then activate TRP channels [reviewed in [72]]. An interesting feature of RDGA is that in photoreceptors, the protein is localized to the sub-microvillar cisternae (SMC) [73], a specialization of the ER that forms a membrane contact site with the microvillar plasma membrane [reviewed in [74]] This localization of RDGA to an ER sub-compartment resembles, conceptually, the recruitment of DGK and DGK from the ER to the PM of mammalian cells following receptor-mediated PLC activation. In the case of Drosophila photoreceptors, RDGA could act in trans across the small 10 nm gap at this MCS to access DG generated at the microvillar plasma membrane by NORPA.…”
Section: Diacylglycerol Kinasesmentioning
confidence: 99%